Drug Addiction and Families. - Barnard, Marina, 1960- (Jessica Kingsley Publishers, 2006)
Drug problems have a profound impact on families. Mothers and fathers, brothers, sisters and children are frequently caught in the maelstrom that drug problems almost inevitably create. Within the UK there is a serious lack of information on the experiences of families attempting to live and cope with a family members' drug problem. Drug Addiction and Families is an exploration of the impact of drug use on families, and of the extent to which current practice meets the needs of families as well as problem drug users. Drawing on a substantial research study comprising interviews with problem dr.